Climate anomalies and competition reduce establishment success during island colonization. Issue 10 (8th October 2022) - Nicholson, Daniel J.; Knell, Robert J.; McCrea, Rachel S.; Neel, Lauren K.; Curlis, John David; Williams, Claire E.; Chung, Albert K.; McMillan, William Owen; Garner, Trenton W. J.; Cox, Christian L.; Logan, Michael L.
Abstract: Understanding the factors that facilitate or constrain establishment of populations in novel environments is crucial for conservation biology and the study of adaptive radiation. Important questions include: (1) Does the timing of colonization relative to stochastic events, such as climatic perturbations, impact the probability of successful establishment? (2) To what extent does community context (e.g., the presence of competitors) change the probability of establishment? (3) How do sources of intrapopulation variance, such as sex differences, affect success at an individual level during the process of establishment? Answers to these questions are rarely pursued in a field‐experimental context or on the same time scales (months to years) as the processes of colonization and establishment. We introduced slender anole lizards ( Anolis apletophallus ) to eight islands in the Panama Canal and tracked them over multiple generations to investigate the factors that mediate establishment success. All islands were warmer than the mainland (ancestral) environment, and some islands had a native competitor. We transplanted half of these populations only 4 months before the onset of a severe regional drought and the other half 2 years (two generations) before the drought. We found that successful establishment depended on both the intensity of interspecific competition and the timing of colonization relative to the drought. The islands that were colonized shortly before the drought went functionally extinct by the second generation, and regardless of time before the drought, the populations on islands with interspecific competition declined continuously over the study period. Furthermore, the effect of the competitor interacted with sex, with males suffering, and females benefitting, from the presence of a native competitor. Our results reveal that community context and the timing of colonization relative to climactic events can combine to determine establishment success and that these factors can generate opposite effects on males and females. Abstract : Our results reveal that community context and the timing of colonization relative to climatic events can combine to determine establishment success.